PERDAGANGAN INTERNASIONAL: MODEL HECKSCHER-OHLIN - Dwi Anggraini; Hana Salsabila, Na’imi Salwa Purba, Raehanun Aisyah Fitri, Zhafirah Salsabila; Dwita Sakuntala (CV. ADIBA AISHA AMIRA, 2025)
This study analyzes the application of the Heckscher-Ohlin Theory (HO) in international trade, which explains trade patterns based on the relative scarcity of production factors, such as labor and capital. Using a descriptive qualitative method with a literature review approach, this study examines the relevance of HO theory in the context of Indonesian trade. The results show that Indonesia, with its comparative advantage in natural resource commodities, needs to increase competitiveness through innovation and product diversification. International trade provides economic benefits, but it also creates challenges such as global market dependence. Appropriate trade policies are needed to optimize benefits, mitigate risks, and support inclusive and sustainable economic development